The Influence of Teacher Performance and School Environment on Elementary School Students Learning Outcomes in Cluster 1 Tikala District Manado City - Miranda Christina Selvy Bella; Philotheus E. A. Tuerah; Juliana Margareta Sumilat (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study aims to analyze the influence of teacher performance and school environment on elementary school students’ learning outcomes in Cluster 1, Tikala District,Manado City. The research employed aquantitative approach using a survey method to obtain empirical data regarding the relationships among the variables studied. The research subjects were elementary school teachers in Cluster 1, Tikala District, Manado City, selected using proportional sampling to ensure that each school had a proportional opportunity to be included in the sample. Data were collected through questionnaires as research instruments, which had previously undergone validity and reliability testing to ensure their appropriateness. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS as a statistical analysis tool. The results indicate that teacher performance has a significant effect on students’ learning outcomes, and the school environment also significantly influences students’ learning outcomes. Simultaneously, teacher performance and school environment contribute significantly to improving students’ learning outcomes. These findings suggest that the improvement of students’ learning outcomes is influenced not only by teachers’ professionalism in implementing the learning process but also by the creation of a conducive, safe, and supportive school environment that enhances the effectiveness of teaching and learning activities.